2017
DOI: 10.20853/31-4-1330
|View full text |Cite
|
Sign up to set email alerts
|

Studying sexuality: LGBTI experiences in institutions of higher education in Southern Africa

Abstract: Although there are several studies internationally on gender and sexual orientation diversity, these are limited in the Southern African Development Community (SADC). This special issue contains articles written from different Institutions of Higher Education (IHE) in the SADC region on experiences of LGBTI individuals covering sexual health, teaching and training, advocacy and interventions. The aim of publishing this research is to disseminate information for broader advocacy to destabilise hetero-and cis-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…The current article echoes the call for a localised focus on the experiences of and possibilities for gender and sexually diverse persons in education institutions in the global South (Graziano 2004;Nduna et al 2017). The writers engage the findings from a 2017 explorative sociological study on the need for such safe spaces for lesbian and gay students on North-West University's (NWU) Potchefstroom campus.…”
Section: Introductionmentioning
confidence: 89%
“…The current article echoes the call for a localised focus on the experiences of and possibilities for gender and sexually diverse persons in education institutions in the global South (Graziano 2004;Nduna et al 2017). The writers engage the findings from a 2017 explorative sociological study on the need for such safe spaces for lesbian and gay students on North-West University's (NWU) Potchefstroom campus.…”
Section: Introductionmentioning
confidence: 89%
“…When apartheid ended more than two decades ago, the new government in South Africa quickly adopted progressive legislation, passing laws that enshrine gender equality and freedom of expression (De Greef 2019). Despite the fact that South Africa passed a Bill of Rights in 1996 that forbids discrimination against individuals on the grounds of sexual orientation, the LGBTQ community still suffers homophobia, particularly in townships and rural areas (Nduna et al 2017). A study conducted by Hosken (2017) found that approximately 50% of the respondents knew and/or had heard of a gay individual who has been assaulted, raped or murdered for being gay.…”
Section: Tolerance Towards Homosexuality In South Africamentioning
confidence: 99%
“…Within psychology programs, help to fill a theoretical and training gap by providing incentives to explore LGBTQ issues in different areas of psychology (e.g., include openness to exploring LGBTQ concerns in course objectives and allow students to focus on LGBTQ issues in their research). In this regard, Southern Africa has indeed seen an increase in publications addressing the need for more inclusive pedagogical and research practices, aimed at challenging heteronormativity (Francis & Msibi, 2011;Nduna, Mthombeni, Mavhandu-Mudzusi, & Mogotsi, 2017;Nel, 2009b).…”
Section: Recommendationsmentioning
confidence: 99%